Virgin coconut oil (VCO) and potassium glycinate (PG) mixture as absorbent for carbon dioxide capture - Mohsin, H.M. (Elsevier Ltd, 2018)
In this work, the performance of potassium glycinate (PG) and virgin coconut oil (VCO) mixture as potential green solvent for carbon dioxide (CO2) capture was investigated. The mixture was prepared by mixing PG with 50 weight percent (w/w) VCO and characterised using density meter, tensiometer and Fourier Transform Infrared (FT-IR) spectrometer. The densities of PG, VCO and PG-VCO mixtures measured from 303.15 to 333.15 K were fitted against an empirical correlation. Viscosities of pure VCO and PG-VCO mixtures were measured at 308.15 K. The solubility of absorbents were studied by bubbling CO2 directly into the solution and measuring mass increase of the solution. Experimental results showed that the density of PG, VCO, and PG-VCO mixtures decreased with increase in temperature and increased with increase in PG concentration. On the other hand, the viscosity of PG-VCO mixtures were reduced by approximately half compared to pure VCO. Moreover, the addition of VCO into the PG solution enhanced the solubility of CO2 in the mixture due to the additional physical interaction between VCO and CO2 molecules. Maximum CO2 absorption of 3.942 mol CO2/mol of PG was observed for 0.1 M PG-VCO mixture. A mechanism study also revealed that the presence of VCO contributed to the formation of bicarbonate ion and protonated potassium glycinate after the CO2 absorption. Â© 2018